Ventilação para conforto térmico de bovinos: mercado leiteiro brasileiro - Ota, Renato Espin [UNESP] (2018)
The dairy sector has an important role in the economic and social order of the Brazilian agri-business, with a significant participation in the livestock GDP. Brazilian production shows an-nual growth above the world average, which guarantees Brazil the fourth position in the ranking of the world's largest milk producers. The productive sector has a universe of 1.3 million dairy farms. Yet we are in 96th place in terms of productivity. This shows the undeniable trend of transition from milk production systems to methods with high efficiency and quality. The Com-post Barn is an excellent alternative for the Brazilian market, being a method with high produc-tivity and relatively low investment cost. Its main characteristics are the guarantee of dry and ventilated space throughout the year, and a bed of sawdust that allows greater comfort for the animals, who need quiet space to perform rumination. In addition, the Compost Barn is a prac-tice adequate to the current animal welfare requirements, which value the rational management that guarantees the physical integrity of the herd without subjecting the cows to unnecessary stress conditions. The objective of this work is to study the application of EC Axial Fans for the thermal comfort of cattle in the Compost Barn confinement system. In order to develop a comparative study, using concepts of ventilation and heat transfer, between the types of instal-lation and technology, traditional and modern, for the ventilation of cattle for production of milk with high efficiency